Peningkatan Aktivitas Belajar PKN Melalui Penerapan Model Pembelajaran Bermain Peran Pada Siswa Sma Negeri 1 Kecamatan Payakumbuh - Yuhasnil Yuhasnil; Sintawati Sintawati (IJOCE: Indonesia Journal of Civic Education, 2020)
The purpose of this study was to increase PKN learning activities through the application of role playing learning models for grade X / 6 students of SMA Negeri 1 Payakumbuh District. This type of research is Classroom Action Research (CAR), by collecting data using observations and field notes. The results of this study indicate that there is a significant improvement using role playing learning models. This model is carried out in 2 cycles and each consists of two meetings. Based on the weaknesses or deficiencies seen in the implementation of learning in the first cycle, better learning is planned in the second cycle, so that the increase in student activity that occurs is truly significant. The increase in PKN learning activities seen in Prasiklus research results was 17.2% with low criteria, the first cycle the average number of students active in the learning process was 46.8% with sufficient criteria, and in the second cycle the average number of active students in the learning process is 60.9% with high criteria. The conclusion of this study is that there is an increase in students' learning after using role playing learning models. Keywords: Learning Activities, Role Playing Learning Models.